2020
DOI: 10.1007/s11092-020-09330-y
|View full text |Cite|
|
Sign up to set email alerts
|

Teachers responding to cultural diversity: case studies on assessment practices, challenges and experiences in secondary schools in Austria, Ireland, Norway and Turkey

Abstract: Global mobility and economic and political crises in some parts of the world have fuelled migration and brought new constellations of 'cultural diversity' to European classrooms (OECD 2019). This produces new challenges for teaching, but also for assessment in which cultural biases may have far-reaching consequences for the students' further careers in education, occupation and life. After considering the concept of and current research on 'culturally responsive assessment', we use qualitative interview data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 42 publications
1
28
0
5
Order By: Relevance
“…Teacher support is one the most crucial ones; when the perceived teacher support is high, children might perceive less prejudice than when they feel they are not supported well by their teachers (Miklikowska et al, 2019). However, in one of the recent comparative studies, teachers reported that cultural diversity is a difficult concept that needs further clarification and teaching in a multicultural classroom and they need additional skills (Herzog-Punzenberger et al, 2020). Therefore, it was suggested that a school policy on diversity might help teachers to better adapt culturally responsive practices in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Teacher support is one the most crucial ones; when the perceived teacher support is high, children might perceive less prejudice than when they feel they are not supported well by their teachers (Miklikowska et al, 2019). However, in one of the recent comparative studies, teachers reported that cultural diversity is a difficult concept that needs further clarification and teaching in a multicultural classroom and they need additional skills (Herzog-Punzenberger et al, 2020). Therefore, it was suggested that a school policy on diversity might help teachers to better adapt culturally responsive practices in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Las estructuras institucionales son expresión de las orientaciones y los valores básicos de la práctica diaria de docentes y de la administración escolar. Tras analizar las prácticas de evaluación en cuatro países distintos (Austria, Irlanda, Noruega y Turquía), era obvio que las prácticas culturalmente sensibles y, por tanto, adaptadas al estudiante (inmigrante) individual son las más difíciles de implementar por los profesores en sistemas escolares altamente selectivos como los descritos anteriormente en el caso de Austria (Herzog-Punzenberger et al, 2020). Puesto que el profesor o profesora trabaja hacia una clase homogénea y, para ello, tiene que identificar estudiantes que dirige hacia un nivel inferior o a repetir el curso, este se encuentra constantemente bajo presión para justificar estas decisiones.…”
Section: Tipología Del Contexto De Integración Escolarunclassified
“…Above all, culturally competent knowledge exchange enables partnerships where instructors across countries can contextualize and optimize the implementation of evidence-based teaching practices developed in one part of the world within their own teaching ( 16 ). It is equally important that western academics learn from other cultures to teach to a global student base ( 17 , 18 ). We therefore propose that cross-cultural professional development activities also present themselves as avenues for refining global cultural awareness.…”
Section: Introductionmentioning
confidence: 99%